Web-Age Information Management 17th International Conference, WAIM 2016, Nanchang, China, June 3-5, 2016, Proceedings, Part II - Cui, Bin; Zhang, Nan; Xu, Jianliang; Lian, Xiang; Liu, Dexi (Information Systems and Applications, incl. Internet/Web, and HCI, 2016)
This two-volume set, LNCS 9658 and 9659, constitutes the thoroughly refereed proceedings of the 17th International Conference on Web-Age Information Management, WAIM 2016, held in Nanchang, China, in June 2016. The 80 full research papers presented together with 8 demonstrations were carefully reviewed and selected from 266 submissions. The focus of the conference is on following topics: data mining, spatial and temporal databases, recommender systems, graph data management, information retrieval, privacy and trust, query processing and optimization, social media, big data analytics, and distributed and cloud computing.